The actin domain of Gardner-Rasheed feline sarcoma virus inhibits kinase and transforming activities. - Sugita, K (1989)
The transforming gene product, P70gag-actin-fgr, of Gardner-Rasheed feline sarcoma virus (GR-FeSV) is a single polypeptide composed of regions derived from cellular and viral genes. Gamma actin and c-fgr genes are the two known cellular components of the GR-FeSV genome. In the present study, sequences representing each cell-derived gene were deleted and the resulting constructs were tested for transforming activity by transfection of NIH 3T3 cells. Constructs lacking a portion of the c-fgr proto-oncogene failed to induce focus formation, demonstrating the essential nature of this component for GR-FeSV oncogenic activity. In contrast, the construct lacking the actin domain was more active than GR-FeSV DNA in transformation assays. Protein specified by the actin deletion mutant possessed a 2.4-fold greater specific protein-tyrosine kinase activity compared with that of the wild-type gene product. Furthermore, the actin domain had no detectable effect on the ability of the fgr kinase to associate with cytoskeleton or to phosphorylate unique cellular proteins on tyrosine. Our findings demonstrate that the actin domain inhibits focus formation and impairs protein-tyrosine kinase activity.